Parametric investigation of concrete solar collectors for façade integration. (1st September 2017) - O'Hegarty, Richard; Kinnane, Oliver; McCormack, Sarah J.
Highlights: Concrete solar collector's performance compare well with other types of unglazed collectors. A 2D finite element model of a concrete solar collector is presented and validated. Concrete solar collector parameters are individually investigated. Concrete conductivity and concrete solar absorptance are experimentally measured. Practical, economic and aesthetical design limitations are discussed. Abstract: Concrete solar collectors are a cheap and durable option for solar thermal energy harvesting for hot water and space heating applications. They offer a unique facade integrated solar thermal solution, allowing for seamless integration with precast concrete cladding systems. The thermal energy output of a concrete solar collector is dictated by its material (thermal conductivity and specific heat capacity of concrete and pipe), geometry (pipe spacing, pipe diameter, collector thickness, pipe embedment depth) surface finish (absorptance and emittance) and fluid flow. Given the wide range of individual parameter values documented in the literature an investigation into these parameters is required. In this work concrete solar collectors are simulated using an experimentally validated 2D finite element model computed in COMSOL Multiphysics. Outlet fluid temperatures up to 40 °C and a daily efficiency of 56% are predicted for a clear summer day in Ireland using the model for a reference case concrete solar collector. Concrete solar collectors compare well with other unglazed collectors (metallic absorber; daily efficiency = 62%) and (polymer absorber; daily efficiency = 29%). Parameters are investigated individually and compared collectively within the range of values found in the literature. Concrete conductivity and solar absorptance are highlighted as two influential performance parameters which can be improved and are subsequently investigated experimentally. Additionally, geometric parameters, including the embedment depth and pipe spacing are identified as key performance parameters. These material and geometric parameters are limited by practical, economic and aesthetical constraints. These limitations are also examined and summarised.